Preparation process of impact-resistant ABS modified plastic
By adding specific formulas of impact modifiers to ABS resin, the problem of poor impact resistance of ABS plastics is solved, and the efficient impact resistance of the material is improved and cost control is achieved.
Patent Information
- Application Number
- CN202510074137.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
The impact resistance of existing ABS plastics is poor, the existing methods are costly and the process conditions are difficult to control.
By adding lubricant, antioxidant and impact modifier to the ABS resin, the impact modifier is obtained from mixing the ethylene-acrylate-glycidyl methacrylate terpolymer, acrylonitrile-butadiene-styrene-styrene-grafted maleic anhydride with a light rod waste hydrophobic modified powder, which enhances the compatibility and mechanical strength of the material through chemical bonding and physical filling.
It significantly improves the impact strength and overall mechanical properties of ABS, reduces the cost of compounding, and avoids the decline in material performance caused by additive loss.
Smart Images

Figure BDA0005246536900000111 
Figure BDA0005246536900000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a preparation process of impact-resistant ABS modified plastics. Background Art
[0002] ABS resin is an important general synthetic resin, mainly a blend or terpolymer of acrylonitrile, butadiene and styrene. Among them, the addition of acrylonitrile provides ABS with high hardness and strength, heat resistance and corrosion resistance; butadiene gives ABS high impact resistance, toughness, cold resistance and certain ductility; and styrene ensures ABS's good surface gloss, easy coloring and easy processing. ABS is a thermoplastic polymer material with high strength, good toughness and easy processing. It has a wide range of uses. The automotive industry often uses it to manufacture automotive parts such as dashboards, body panels, interior trim panels, steering wheels, etc. The home appliance industry often uses it to manufacture refrigerators, televisions, vacuum cleaners, etc. The construction industry often uses it to manufacture sanitary ware, swimming pool linings, pipes and pipe fittings, etc. It is also used to manufacture helmets, motorcycle fenders, toys, clocks, cosmetic boxes, etc.
[0003] ABS resin can be processed into plastics by injection molding, extrusion, vacuum, blow molding and roller pressing, and can also be processed by mechanical, bonding, coating, vacuum evaporation and other methods. Due to its excellent comprehensive performance, it has a wide range of uses. It is mainly used as an engineering material and can also be used for household appliances. Due to its good oil resistance, acid, alkali, salt and chemical reagent resistance, and electroplating properties, it has the advantages of good gloss, light specific gravity and low price after being plated with a metal layer, and can be used to replace certain metals. It can also be synthesized into many varieties such as self-extinguishing type and heat-resistant type to adapt to various uses.
[0004] ABS resin has good mechanical properties, but in some special fields, the material needs to have better impact resistance. The existing method often uses a grafting method to graft ABS resin, but the process conditions are difficult to control and the cost is high.
[0005] In the prior art, for example, patent document CN102382388B discloses a PVC / ABS alloy material with high impact strength and a preparation method thereof. In the invention, the alloy material is composed of 30%-80% of a PVC composite material modified by active nano-calcium carbonate filling and 20%-70% of an injection-grade ABS resin in a weight ratio. The PVC composite material includes PVC resin, a heat stabilizer, a lubricant, an impact modifier, an antioxidant, a flame retardant and a filler active nano-calcium carbonate, and its weight ratio is: PVC resin: heat stabilizer: impact modifier: lubricant: antioxidant: flame retardant: filler = 100 parts: 4.7-5.5 parts: 5-15 parts: 0.1-6 parts: 0.1-2 parts: 3-6 parts: 5-20 parts; in the invention, PVC and ABS resin are compounded to improve the impact resistance of ABS resin, but a large amount of filler needs to be added during the compounding process, resulting in high compounding cost. There is a problem of loss of additives during use, resulting in a decrease in material performance, and the impact resistance of ABS plastics needs to be improved.
[0006] Therefore, according to the above-mentioned related technologies, it is urgent to develop a process for preparing impact-resistant ABS modified plastics. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a process for preparing impact-resistant ABS modified plastics to solve the problem of poor impact resistance of ABS plastics in the prior art.
[0008] Based on the above purpose, the present invention provides a process for preparing impact-resistant ABS modified plastic.
[0009] A process for preparing impact-resistant ABS modified plastics, comprising the following raw materials in parts by weight:
[0010] ABS resin 100-120 parts, lubricant 5-7 parts, antioxidant 2-5 parts, impact modifier 2-6 parts;
[0011] The impact modifier is obtained by mixing ethylene-acrylate-glycidyl methacrylate terpolymer, acrylonitrile-butadiene-styrene grafted maleic anhydride and light rod waste hydrophobic modified powder in a mass ratio of 5-7:18-22:10-14.
[0012] Preferably, the preparation method of the acrylonitrile-butadiene-styrene grafted maleic anhydride is as follows:
[0013] Step A1. Dry ABS in a vacuum oven at 60-65°C for 22-24h, add maleic anhydride and dicumyl peroxide, place in a torque rheometer, adjust parameters under air atmosphere, and grind with a knife grinder to obtain a mixture A;
[0014] Step A2. Dissolve the mixture A in tetrahydrofuran, heat to reflux, vacuum filter, add methanol for washing, and then vacuum dry to obtain acrylonitrile-butadiene-styrene grafted maleic anhydride.
[0015] Preferably, in step A1, the mass ratio of ABS, maleic anhydride and dicumyl peroxide is 100-120:2.8-3.7:0.35-0.45;
[0016] The parameters include a rotation speed of 50-70 rpm, a temperature of 210-230° C., and a reaction time of 8-12 min.
[0017] Preferably, the ratio of the mixture A to tetrahydrofuran in step A2 is 10-14 g: 200-280 mL.
[0018] Preferably, the temperature during heating and reflux in step A2 is 105-120° C. and the time is 100-120 min;
[0019] The vacuum drying is carried out at a temperature of 50-60°C and for a time of 24-26 hours.
[0020] Preferably, the preparation method of the hydrophobically modified powder of waste light rods is as follows:
[0021] Step B1. Dry the waste optical fiber preform at 80-90°C, crush it, and sieve it to obtain 50-60 mesh pellets, then roast it, take it out and place it in a dryer to cool it naturally to obtain nano powder;
[0022] Step B2. After the nano powder is placed in a drying oven for activation treatment, xylene and silane coupling agent KH-560 are added for heating and reflux, and the hydrophobic modified powder of the waste light rod is obtained after centrifugation, washing and drying.
[0023] Preferably, the calcination temperature in step B1 is 500-600° C. and the calcination time is 1.5-2.5 h;
[0024] The activation treatment in step B2 is carried out at a temperature of 150-160° C. and for a time of 12-14 hours.
[0025] Preferably, the mass ratio of the nano powder, xylene and silane coupling agent KH-560 in step B2 is 4-8:25-38:5-12;
[0026] The temperature during heating and reflux in step B2 is 110-120° C. and the time is 6.5-7.5 h.
[0027] Preferably, the antioxidant is antioxidant 1076, antioxidant DNP or antioxidant CA;
[0028] The lubricant is any one of zinc stearate and ethylene bisstearamide.
[0029] Preferably, the method comprises the following steps:
[0030] Step S1. Ethylene-acrylate-glycidyl methacrylate terpolymer, acrylonitrile-butadiene-styrene grafted maleic anhydride and hydrophobically modified powder of waste light rods are placed in a low-speed mixer and mixed for 5-8 minutes to obtain an impact modifier, and then ABS resin is added and mixed for 10-15 minutes, and then a lubricant and an antioxidant are added and mixed for 20-30 minutes to obtain a mixture B;
[0031] Step S2: placing the mixture B in a twin-screw extruder, melt-blending and extruding at 120° C.-135° C., and cutting into pellets by a plastic pelletizer to obtain impact-resistant ABS modified plastic.
[0032] Beneficial effects of the present invention:
[0033] The invention provides a process for preparing impact-resistant ABS modified plastic. The invention obtains ABS modified plastic with excellent impact resistance by adding a lubricant, an antioxidant and an impact modifier into ABS resin. The impact modifier is obtained by mixing ethylene-acrylate-methacrylate glycidyl ester terpolymer, acrylonitrile-butadiene-styrene grafted maleic anhydride and light rod waste hydrophobic modified powder. The ethylene-acrylate-methacrylate glycidyl ester terpolymer and acrylonitrile-butadiene-styrene grafted maleic anhydride improve the compatibility and toughness of the material through chemical bonding, while the light rod waste hydrophobic modified powder enhances the mechanical strength of the ABS resin through physical filling and chemical cross-linking. The three substances work together after being mixed, which not only improves the impact resistance of the ABS, but also improves the overall mechanical properties of the material. Compared with the prior art, the invention has broad application prospects. DETAILED DESCRIPTION
[0034] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0035] The sources and properties of some of the raw materials used in the present invention are as follows:
[0036] Ethylene-acrylate-glycidyl methacrylate terpolymer was purchased from Zhangjiagang Chuangli New Materials Co., Ltd.; ABS resin was purchased from Shandong Jiumiao Materials Technology Co., Ltd.; maleic anhydride was purchased from Guangzhou Haoyu International Trade Co., Ltd.; diisopropylbenzene peroxide was purchased from Norlis Chemicals (Ningbo) Co., Ltd.; tetrahydrofuran was purchased from Hebei Meibang Engineering Technology Co., Ltd.; methanol was purchased from Sichuan Guanghan Jinyan Fireworks Co., Ltd.; xylene Jiangsu Plus Biotechnology Co., Ltd.; silane coupling agent KH-560 was purchased from Guangdong Innovation Coupling Agent Chemical Co., Ltd.
[0037] Embodiment 1: A process for preparing impact-resistant ABS modified plastics, comprising the following steps:
[0038] S1. 100 g ABS was placed in a vacuum oven at 60 ° C and dried for 22 h, 2.8 g maleic anhydride and 0.35 g dicumyl peroxide were added, placed in a torque rheometer, and the speed was adjusted to 50 rpm, the temperature was 210 ° C, and the reaction time was 8 min under air atmosphere, and then ground with a knife grinder to obtain a mixture A;
[0039] S2. 10 g of mixture A was dissolved in 200 mL of tetrahydrofuran, heated under reflux at 105° C. for 100 min, vacuum filtered, washed with methanol, and then vacuum dried at 50° C. for 24 h to obtain acrylonitrile-butadiene-styrene grafted maleic anhydride;
[0040] S3. The waste optical fiber preform was dried at 80°C, crushed, and sieved to obtain 50-60 mesh pellets, which were then calcined at 500°C for 1.5h, taken out and placed in a dryer to cool naturally to obtain a nanopowder;
[0041] S4. 4 g of nanopowder was placed in a drying oven, activated at 150 ° C for 12 h, and then 25 g of xylene and 5 g of silane coupling agent KH-560 were added and heated to reflux at 110 ° C for 6.5 h, centrifuged, washed and dried to obtain a hydrophobic modified powder of light rod waste;
[0042] S5. 5 g of ethylene-acrylate-glycidyl methacrylate terpolymer, 18 g of acrylonitrile-butadiene-styrene grafted maleic anhydride and 10 g of light rod waste hydrophobic modified powder were placed in a low-speed mixer and mixed for 5 min to obtain an impact modifier, 2 g of the impact modifier was taken, 100 g of ABS resin was added and mixed for 10 min, and then 5 g of ethylene bisstearamide and 2 g of antioxidant DNP were added and mixed for 20 min to obtain a mixture B;
[0043] S6. Place the mixture B in a twin-screw extruder, melt-blend and extrude at 120° C., and cut it into pellets using a plastic pelletizer to obtain impact-resistant ABS modified plastic.
[0044] Embodiment 2: A process for preparing impact-resistant ABS modified plastics, comprising the following steps:
[0045] S1. 104 g ABS was placed in a vacuum oven at 62 ° C and dried for 22.5 h, 3 g maleic anhydride and 0.37 g dicumyl peroxide were added, placed in a torque rheometer, and the speed was adjusted to 55 rpm, the temperature was 215 ° C, and the reaction time was 9 min under air atmosphere, and then ground with a knife grinder to obtain a mixture A;
[0046] S2. 11 g of mixture A was dissolved in 210 mL of tetrahydrofuran, heated under reflux at 108° C. for 105 min, vacuum filtered, washed with methanol, and then vacuum dried at 52° C. for 24.5 h to obtain acrylonitrile-butadiene-styrene grafted maleic anhydride;
[0047] S3. The waste optical fiber preform was dried at 82°C, crushed, and sieved to obtain 50-60 mesh pellets, which were then calcined at 510°C for 1.5h, taken out and placed in a dryer to cool naturally to obtain a nanopowder;
[0048] S4. 5 g of nanopowder was placed in a drying oven, activated at 152 ° C for 12.5 h, and then 27 g of xylene and 6 g of silane coupling agent KH-560 were added and heated to reflux at 112 ° C for 6.5 h, centrifuged, washed and dried to obtain a hydrophobic modified powder of light rod waste;
[0049] S5. 5.5g of ethylene-acrylate-glycidyl methacrylate terpolymer, 18.5g of acrylonitrile-butadiene-styrene grafted maleic anhydride and 10.5g of light rod waste hydrophobic modified powder were placed in a low-speed mixer and mixed for 5min to obtain an impact modifier, 2.5g of the impact modifier was taken, and 105g of ABS resin was added and mixed for 12min, and then 5.5g of ethylene bisstearamide and 2.5g of antioxidant DNP were added and mixed for 22min to obtain a mixture B;
[0050] S6. Place the mixture B in a twin-screw extruder, melt-blend and extrude at 123° C., and cut it into pellets using a plastic pelletizer to obtain impact-resistant ABS modified plastic.
[0051] Embodiment 3: A process for preparing impact-resistant ABS modified plastics, comprising the following steps:
[0052] S1. 108 g ABS was placed in a vacuum oven at 62 ° C and dried for 22.5 h, 3.2 g maleic anhydride and 0.39 g dicumyl peroxide were added, placed in a torque rheometer, and the speed was adjusted to 60 rpm, the temperature was 220 ° C, the reaction time was 10 min, and then ground with a knife grinder to obtain a mixture A;
[0053] S2. 11.5 g of mixture A was dissolved in 220 mL of tetrahydrofuran, heated under reflux at 110° C. for 108 min, vacuum filtered, washed with methanol, and then vacuum dried at 54° C. for 24.5 h to obtain acrylonitrile-butadiene-styrene grafted maleic anhydride;
[0054] S3. The waste optical fiber preform was dried at 84°C, crushed, and sieved to obtain 50-60 mesh pellets, which were then calcined at 540°C for 2h, taken out and placed in a dryer to cool naturally to obtain a nano powder;
[0055] S4. 5 g of nanopowder was placed in a drying oven, activated at 154 ° C for 13 h, and then 30 g of xylene and 7 g of silane coupling agent KH-560 were added and heated under reflux at 114 ° C for 7 h, centrifuged, washed and dried to obtain a hydrophobic modified powder of light rod waste;
[0056] S5. 6 g of ethylene-acrylate-glycidyl methacrylate terpolymer, 19 g of acrylonitrile-butadiene-styrene grafted maleic anhydride and 11 g of hydrophobic modified powder of light rod waste were placed in a low-speed mixer and mixed for 6 min to obtain an impact modifier, 3 g of the impact modifier was taken, and 108 g of ABS resin was added and mixed for 12 min, and then 6 g of ethylene bisstearamide and 3 g of antioxidant DNP were added and mixed for 24 min to obtain a mixture B;
[0057] S6. Place the mixture B in a twin-screw extruder, melt-blend and extrude at 125° C., and cut it into pellets using a plastic pelletizer to obtain impact-resistant ABS modified plastic.
[0058] Embodiment 4: A process for preparing impact-resistant ABS modified plastics, comprising the following steps:
[0059] S1. 112 g ABS was placed in a vacuum oven at 64 ° C and dried for 23 h, 3.4 g maleic anhydride and 0.41 g dicumyl peroxide were added, placed in a torque rheometer, and the speed was adjusted to 65 rpm, the temperature was 222 ° C, and the reaction time was 10 min under air atmosphere, and then ground with a knife grinder to obtain a mixture A;
[0060] S2. 12 g of the mixture A was dissolved in 250 mL of tetrahydrofuran, heated under reflux at 112° C. for 112 min, vacuum filtered, washed with methanol, and then vacuum dried at 56° C. for 25 h to obtain acrylonitrile-butadiene-styrene grafted maleic anhydride;
[0061] S3. The waste optical fiber preform was dried at 86°C, crushed, and sieved to obtain 50-60 mesh pellets, which were then calcined at 560°C for 2h, taken out and placed in a dryer to cool naturally to obtain a nano powder;
[0062] S4. 6 g of nanopowder was placed in a drying oven, activated at 156 ° C for 13 h, and then 34 g of xylene and 8 g of silane coupling agent KH-560 were added and heated under reflux at 116 ° C for 7 h, centrifuged, washed and dried to obtain a hydrophobic modified powder of light rod waste;
[0063] S5. 6.5 g of ethylene-acrylate-glycidyl methacrylate terpolymer, 20 g of acrylonitrile-butadiene-styrene grafted maleic anhydride and 12 g of light rod waste hydrophobic modified powder were placed in a low-speed mixer and mixed for 7 min to obtain an impact modifier, 4 g of the impact modifier was taken, 112 g of ABS resin was added and mixed for 14 min, 6 g of ethylene bisstearamide and 4 g of antioxidant DNP were added and mixed for 26 min to obtain a mixture B;
[0064] S6. Place the mixture B in a twin-screw extruder, melt-blend and extrude at 128° C., and cut it into pellets using a plastic pelletizer to obtain impact-resistant ABS modified plastic.
[0065] Embodiment 5: A process for preparing impact-resistant ABS modified plastics, comprising the following steps:
[0066] S1. 118 g ABS was placed in a vacuum oven at 65 ° C and dried for 23.5 h, 3.5 g maleic anhydride and 0.43 g dicumyl peroxide were added, placed in a torque rheometer, and the speed was adjusted to 65 rpm, the temperature was 225 ° C, the reaction time was 11 min, and then ground with a knife grinder to obtain a mixture A;
[0067] S2. 13 g of the mixture A was dissolved in 260 mL of tetrahydrofuran, heated under reflux at 117° C. for 115 min, vacuum filtered, washed with methanol, and then vacuum dried at 58° C. for 25.5 h to obtain acrylonitrile-butadiene-styrene grafted maleic anhydride;
[0068] S3. The waste optical fiber preform was dried at 88°C, crushed, and sieved to obtain 50-60 mesh pellets, which were then calcined at 580°C for 2.5h, taken out and placed in a dryer to cool naturally to obtain a nanopowder;
[0069] S4. 7.5 g of nanopowder was placed in a drying oven, activated at 158 ° C for 13.5 h, and then 36 g of xylene and 10 g of silane coupling agent KH-560 were added and heated to reflux at 118 ° C for 7.5 h, centrifuged, washed and dried to obtain a hydrophobic modified powder of light rod waste;
[0070] S5. 6.5 g of ethylene-acrylate-glycidyl methacrylate terpolymer, 21 g of acrylonitrile-butadiene-styrene grafted maleic anhydride and 13 g of light rod waste hydrophobic modified powder were placed in a low-speed mixer and mixed for 7 min to obtain an impact modifier, 5 g of the impact modifier was taken, and 118 g of ABS resin was added and mixed for 15 min, and then 7 g of ethylene bisstearamide and 4.5 g of antioxidant DNP were added and mixed for 28 min to obtain a mixture B;
[0071] S6. Place the mixture B in a twin-screw extruder, melt-blend and extrude at 132° C., and cut it into pellets using a plastic pelletizer to obtain impact-resistant ABS modified plastic.
[0072] Embodiment 6: A process for preparing impact-resistant ABS modified plastics, comprising the following steps:
[0073] S1. 120 g ABS was placed in a vacuum oven at 65 ° C and dried for 24 h, 3.7 g maleic anhydride and 0.45 g dicumyl peroxide were added, placed in a torque rheometer, and the speed was adjusted to 70 rpm, the temperature was 230 ° C, and the reaction time was 12 min under air atmosphere, and then ground with a knife grinder to obtain a mixture A;
[0074] S2. 14 g of the mixture A was dissolved in 280 mL of tetrahydrofuran, heated under reflux at 120° C. for 120 min, vacuum filtered, washed with methanol, and then vacuum dried at 60° C. for 26 h to obtain acrylonitrile-butadiene-styrene grafted maleic anhydride;
[0075] S3. The waste optical fiber preform was dried at 90°C, crushed, and sieved to obtain 50-60 mesh pellets, which were then calcined at 600°C for 2.5h, taken out and placed in a dryer to cool naturally to obtain a nanopowder;
[0076] S4. 8 g of nanopowder was placed in a drying oven, activated at 160 ° C for 14 h, and then 38 g of xylene and 5-12 g of silane coupling agent KH-560 were added and heated to reflux at 120 ° C for 7.5 h, centrifuged, washed and dried to obtain a hydrophobic modified powder of light rod waste;
[0077] S5. 7g of ethylene-acrylate-glycidyl methacrylate terpolymer, 22g of acrylonitrile-butadiene-styrene grafted maleic anhydride and 14g of light rod waste hydrophobic modified powder were placed in a low-speed mixer and mixed for 8min to obtain an impact modifier, 6g of the impact modifier was taken, and 120g of ABS resin was added and mixed for 15min, and then 7g of ethylene bisstearamide and 5g of antioxidant DNP were added and mixed for 30min to obtain a mixture B;
[0078] S6. Place the mixture B in a twin-screw extruder, melt-blend and extrude at 135° C., and cut it into pellets using a plastic pelletizer to obtain impact-resistant ABS modified plastic.
[0079] Comparative Example 1:
[0080] Compared with Example 1, the impact modifier was not added in the preparation process of the impact-resistant ABS modified plastic in this comparative example, and the remaining steps and parameters were the same, which will not be repeated in this comparative example, and the impact-resistant ABS modified plastic was finally obtained.
[0081] Comparative Example 2:
[0082] Compared with Example 1, in this comparative example, no hydrophobic modified powder of polished rod waste is added during the preparation process of the impact-resistant ABS modified plastic. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, the impact-resistant ABS modified plastic is obtained.
[0083] Comparative Example 3:
[0084] Compared with Example 1, this comparative example does not add ethylene-acrylate-glycidyl methacrylate terpolymer during the preparation of the impact-resistant ABS modified plastic. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, the impact-resistant ABS modified plastic is obtained.
[0085] Comparative Example 4:
[0086] Compared with Example 1, in this comparative example, acrylonitrile-butadiene-styrene grafted maleic anhydride is not added during the preparation of the impact-resistant ABS modified plastic. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, the impact-resistant ABS modified plastic is obtained.
[0087] Performance Test:
[0088] Determination of thermal conductivity:
[0089] The thermal conductivity was measured with reference to GB3399-82 standard and the instrument used was the KDRX-II transient rapid hot wire method thermal conductivity tester of Xiangtan Xiangyi Instrument Co., Ltd. The impact-resistant ABS modified plastics prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were changed into sheets with a length of 30 mm, a width of 30 mm, and a thickness of 2.5 mm. Before the test, both sides of the sample were evenly coated with thermal conductive glue, the sample was clamped on the upper and lower sides of the sensor, and a certain pressure was applied to fix it. Every 5 samples were tested as a group, and the average value was taken as the test result;
[0090] Notched impact strength performance test:
[0091] With reference to ISO180-1A standard, the impact-resistant ABS modified plastics prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were tested for notched impact strength performance. The impact testing machine automatically calculated the impact strength of the material based on the effective energy absorbed per unit cross-sectional area when the specimen was subjected to load impact and rupture. Ten specimens were selected as a group for each impact test, and the energy at the highest position of the pendulum was 22 J. Finally, the average value of each group of 10 specimens was taken as the test result.
[0092] Table 1
[0093]
[0094]
[0095] Data Analysis:
[0096] As can be seen from Table 1, the impact-resistant ABS modified plastic prepared by the present invention has better impact resistance, which may be due to the impact modifier being obtained by mixing ethylene-acrylate-methacrylate glycidyl terpolymer, acrylonitrile-butadiene-styrene grafted maleic anhydride and light rod waste hydrophobic modified powder, the epoxy group in the ethylene-acrylate-methacrylate glycidyl terpolymer can cross-link with styrene and acrylonitrile in ABS, enhance the binding force between the molecular chains of ABS, improve the impact resistance of the material, and it also has good compatibility, thereby further improving the overall mechanical properties of the material; acrylonitrile-butadiene-styrene grafted maleic anhydride can provide polar groups, increase the surface adhesion and compatibility of ABS materials, and has good elastomeric properties, can absorb energy when impacted, thereby improving the impact strength of ABS; the light rod waste hydrophobic modified powder is a nano-scale particle, which not only improves the mechanical strength of the material, but also enhances the impact resistance of the material, and its surface characteristics also help to reduce friction and wear inside the material, thereby further improving the impact resistance of ABS.
[0097] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0098] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A process for preparing impact-resistant ABS modified plastic, characterized in that: Including the following raw materials by weight: ABS resin 100-120 parts, lubricant 5-7 parts, antioxidant 2-5 parts, impact modifier 2-6 parts; The impact modifier is obtained by mixing ethylene-acrylate-glycidyl methacrylate terpolymer, acrylonitrile-butadiene-styrene grafted maleic anhydride and light rod waste hydrophobic modified powder in a mass ratio of 5-7:18-22:10-14.
2. The process for preparing the impact-resistant ABS modified plastic according to claim 1, characterized in that: The preparation method of the acrylonitrile-butadiene-styrene grafted maleic anhydride is as follows: Step A1. Dry ABS in a vacuum oven at 60-65°C for 22-24h, add maleic anhydride and dicumyl peroxide, place in a torque rheometer, adjust parameters under air atmosphere, and grind with a knife grinder to obtain a mixture A; Step A2. Dissolve the mixture A in tetrahydrofuran, heat to reflux, vacuum filter, add methanol for washing, and then vacuum dry to obtain acrylonitrile-butadiene-styrene grafted maleic anhydride.
3. The process for preparing the impact-resistant ABS modified plastic according to claim 2, characterized in that: In step A1, the mass ratio of ABS, maleic anhydride and dicumyl peroxide is 100-120:2.8-3.7:0.35-0.45; The parameters include a rotation speed of 50-70 rpm, a temperature of 210-230° C., and a reaction time of 8-12 min.
4. The process for preparing the impact-resistant ABS modified plastic according to claim 2, characterized in that: The usage ratio of the mixture A to tetrahydrofuran in step A2 is 10-14 g: 200-280 mL.
5. The process for preparing the impact-resistant ABS modified plastic according to claim 2, characterized in that: The temperature during heating and reflux in step A2 is 105-120° C. and the time is 100-120 min; The temperature during the vacuum drying is 50-60° C. and the time is 24-26 hours.
6. The process for preparing the impact-resistant ABS modified plastic according to claim 1, characterized in that: The preparation method of the hydrophobic modified powder of waste light rods is as follows: Step B1. Dry the waste optical fiber preform at 80-90°C, crush it, and sieve it to obtain 50-60 mesh pellets, then roast it, take it out and place it in a dryer to cool it naturally to obtain nano powder; Step B2: After the nano powder is placed in a drying oven for activation treatment, xylene and silane coupling agent KH-560 are added for heating and reflux, and the hydrophobic modified powder of the waste light rod is obtained after centrifugation, washing and drying.
7. The process for preparing the impact-resistant ABS modified plastic according to claim 6, characterized in that: The calcination temperature in step B1 is 500-600° C. and the calcination time is 1.5-2.5 h; The activation treatment in step B2 is carried out at a temperature of 150-160° C. and for a time of 12-14 hours.
8. The process for preparing the impact-resistant ABS modified plastic according to claim 6, characterized in that: In step B2, the mass ratio of the nano powder to xylene and silane coupling agent KH-560 is 4-8:25-38:5-12; The temperature during heating and reflux in step B2 is 110-120° C. and the time is 6.5-7.5 h.
9. The process for preparing the impact-resistant ABS modified plastic according to claim 1, characterized in that: The antioxidant is antioxidant 1076, antioxidant DNP or antioxidant CA; The lubricant is any one of zinc stearate and ethylene bisstearamide.
10. The process for preparing the impact-resistant ABS modified plastic according to claim 1, characterized in that: The following steps are involved: Step S1. Ethylene-acrylate-glycidyl methacrylate terpolymer, acrylonitrile-butadiene-styrene grafted maleic anhydride and hydrophobically modified powder of waste light rods are placed in a low-speed mixer and mixed for 5-8 minutes to obtain an impact modifier, and then ABS resin is added and mixed for 10-15 minutes, and then a lubricant and an antioxidant are added and mixed for 20-30 minutes to obtain a mixture B; Step S2: placing the mixture B in a twin-screw extruder, melt-blending and extruding at 120° C.-135° C., and cutting into pellets by a plastic pelletizer to obtain impact-resistant ABS modified plastic.
Citation Information
Patent Citations
PVC / ABS alloy material with high anti-impact strength and preparation method thereof
CN102382388B